MULTI-SUBSTRATE RADIOCARBON DATA CONSTRAIN DETRITAL AND RESERVOIR EFFECTS IN HOLOCENE SEDIMENTS OF THE GREAT SALT LAKE, UTAH - Bowen, Gabriel J.; Nielson, Kristine E.; Eglinton, Timothy I. (RADIOCARBON, 2019)
The radiocarbon (C-14) content of simultaneously deposited substrates in lacustrine archives may differ due to reservoir and detrital effects, complicating the development of age models and interpretation of proxy records. Multi-substrate C-14 studies quantifying these effects remain rare, however, particularly for large, terminal lake systems, which are excellent recorders of regional hydroclimate change. We report C-14 ages of carbonates, brine shrimp cysts, algal mat biomass, total organic carbon (TOC), terrestrial macrofossils, and n-alkane biomarkers from Holocene sediments of the Great Salt Lake (GSL), Utah. C-14 ages for co-deposited aquatic organic substrates are generally consistent, with small offsets that may reflect variable terrestrial organic matter inputs to the system. Carbonates and long-chain n-alkanes derived from vascular plants, however, are similar to 1000-4000 C-14 years older than other substrates, reflecting deposition of pre-aged detrital materials. All lacustrine substrates are C-14-depleted compared to terrestrial macrofossils, suggesting that the reservoir age of the GSL was > 1200 years throughout most of the Holocene, far greater than the modern reservoir age of the lake (similar to 300 years). These results suggest good potential for multi-substrate paleoenvironmental reconstruction from Holocene GSL sediments but point to limitations including reservoir-induced uncertainty in( 14)C chronologies and attenuation and time-shifting of some proxy signals due to detrital effects.